Теоретичні та практичні засади лексикографічного опису українсько-німецьких лексичних паралелей - Дубічинський, Володимир Володимирович; Ройтер, Тільманн (Інститут української мови НАН України, 2012)
The article presents a new type of dictionary that describes the semantics of lexical parallels of the Ukrainian and German languages. This dictionary gives an opportunity to present the national-cultural originality of words of the languages under concern in a systematic way. The authors defi ne and illustrate three types of lexical parallels – full, partial, and false parallels – and give a new, non-traditional explanation of "Interlingual Homonyms" and "Interlingual Paronyms".
Theoretical and practical aspects of the lexicographical description of ukrainian-german lexical parallels
Keywords: лексичні паралелі; словник лексичних паралелей; ідіосеми; міжмовна омонімія; міжмовні пароніми; словникова стаття; словники